Preventing 30-day hospital readmissions: a systematic review and meta-analysis of randomized trials - Leppin, Aaron L. (JAMA Intern Med, 2014)
IMPORTANCE: Reducing early (<30 days) hospital readmissions is a policy priority aimed at improving healthcare quality. The Cumulative Complexity Model conceptualizes patient context. It predicts that highly supportive discharge interventions will enhance patient capacity to enact burdensome self-care and avoid readmissions. OBJECTIVES: To synthesize the evidence of the efficacy of interventions to reduce early hospital readmissions and identify intervention features—including their impact on treatment burden and on patients’ capacity to enact post-discharge self-care—that might explain their varying effects. DATA SOURCES: We searched electronic databases (1990 until April 1(st), 2013), contacted experts, and reviewed bibliographies. STUDY SELECTION: Randomized trials that assessed the effect of interventions on all-cause or unplanned readmissions within 30 days of discharge in adult patients admitted to the hospital for a medical or surgical cause for > 24 hours and discharged to home. DATA EXTRACTION AND SYNTHESIS: Reviewer pairs extracted trial characteristics and used an activity-based coding strategy to characterize the interventions; fidelity was confirmed with authors. Blinded to trial outcomes, reviewers noted the extent to which interventions placed additional work on patients after discharge or supported their capacity for self-care in accordance with the Cumulative Complexity Model. MAIN OUTCOME: Relative risk of all-cause or unplanned readmission with or without out of hospital deaths at 30 days post-discharge. RESULTS: In 42 trials, the tested interventions prevented early readmissions [pooled random effects relative risk (RR) 0.82, 95% CI 0.73 to 0.91; p=.03; I(2)= 32%], a finding that was consistent across patient subgroups. Trials published before 2002 reported interventions that were 1.6 times more effective than those tested later (p(interaction) = .01). In exploratory subgroup analyses, interventions with many components (p(interaction) <.01), involving more individuals in care delivery (p(interaction) = .05), and supporting patient capacity for self-care (p(interaction) = .04) were 1.4, 1.3, and 1.3 times more effective than other interventions. A post-hoc regression model showed incremental value in providing comprehensive, post-discharge support to patients and caregivers. CONCLUSIONS: Tested interventions are effective at reducing readmissions, but more effective interventions are complex and support patient capacity for self-care. Interventions tested more recently are less effective. REGISTRATION NUMBER: PROSPERO, CRD42013004773